2003
DOI: 10.1046/j.1528-1157.2003.17602.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy‐induced Changes in Signaling Systems of Human and Rat Postsynaptic Densities

Abstract: Summary:Purpose: To study seizure-induced changes in signaling proteins present in postsynaptic densities (PSDs) isolated from human epileptic neocortex and from rat cortex in which seizures were induced by injection of kainic acid.Methods: We performed Western blot analysis of signaling proteins in PSDs isolated from cortical tissue.Results: Seizures induce a strong upregulation of TrkB, the receptor for brain-derived neurotrophic factor (BDNF), whereas components of the N-methyl-D-aspartate (NMDA)-receptor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…It has also been shown that striatal mRNA of TrkB is transiently elevated after seizures (Merlio et al, 1993;Salin et al, 1995) and that epileptiform activity induces a strong upregulation of cortical TrkB (Wyneken et al, 2001(Wyneken et al, , 2003. All these data support the idea that TrkB/BDNF signaling pathway is a key factor in the development and control of seizures, although the question whether BDNF has a permissive or protective function in the epileptogenesis is still debated.…”
Section: Introductionmentioning
confidence: 62%
“…It has also been shown that striatal mRNA of TrkB is transiently elevated after seizures (Merlio et al, 1993;Salin et al, 1995) and that epileptiform activity induces a strong upregulation of cortical TrkB (Wyneken et al, 2001(Wyneken et al, , 2003. All these data support the idea that TrkB/BDNF signaling pathway is a key factor in the development and control of seizures, although the question whether BDNF has a permissive or protective function in the epileptogenesis is still debated.…”
Section: Introductionmentioning
confidence: 62%
“…In addition, the majority of striatal neurons are inhibitory, and effects of BDNF have been shown to be cell-type-specific Rauskolb et al 2010;Rutherford et al 1998). Furthermore, whether TrkB levels are up or down-regulated or left unaffected after epileptic seizures has been reported to depend on both BDNF levels and the mode of seizure activity (Unsain et al 2009;2008;Wyneken et al 2003;Yokoi et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that neuronal activation, or increases in cAMP and intracellular Ca 2 + , lead to the translocation of TrkB from the cytoplasm to the plasma membrane (MeyerFranke et al, 1998;Ji et al, 2005), and that excitation in experimental and human epilepsy greatly increases the TrkB content in PSDs (Wyneken et al, 2001(Wyneken et al, , 2003. As the increase of TrkB and BDNF is associated with neuronal activation, the decrease of TrkB in PSDs observed here is unlikely to be due to a decreased incorporation, but rather to an increased endocytosis of the BDNF/TrkB complex.…”
Section: Decrease Of Trkb In Psdsmentioning
confidence: 99%